2020
DOI: 10.1038/s41385-019-0245-2
|View full text |Cite
|
Sign up to set email alerts
|

A combination of LCPUFA ameliorates airway inflammation in asthmatic mice by promoting pro-resolving effects and reducing adverse effects of EPA

Abstract: Lipid mediators derived from omega (n)-3 and n-6 long-chain polyunsaturated fatty acids (LCPUFA) play key roles in bronchoconstriction, airway inflammation, and resolution processes in asthma. This study compared the effects of dietary supplementation with either a combination of LCPUFAs or eicosapentaenoic acid (EPA) alone to investigate whether the combination has superior beneficial effects on the outcome of asthmatic mice. Mice were sensitized with house dust mite (HDM) extract, and subsequently supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…DHA and EPA differentially modulate membrane fluidity, lipid oxidation, and signal transduction ( Sherratt and Mason, 2018 ) and are precursors of resolvins, bioactive lipids that control the resolution of inflammation. A combination of EPA and DHA can reduce induced inflammation in mouse models of asthma ( Fussbroich et al, 2020 ). Treatment of F508del CFTR mice with a diet enriched in ω-3 PUFA reduces lung disease ( Portal et al, 2018 ), however, a recent Cochrane meta-analysis of five limited trials did not indicate that ω-3 PUFA dietary supplementation is beneficial for CF patients ( Watson and Stackhouse, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DHA and EPA differentially modulate membrane fluidity, lipid oxidation, and signal transduction ( Sherratt and Mason, 2018 ) and are precursors of resolvins, bioactive lipids that control the resolution of inflammation. A combination of EPA and DHA can reduce induced inflammation in mouse models of asthma ( Fussbroich et al, 2020 ). Treatment of F508del CFTR mice with a diet enriched in ω-3 PUFA reduces lung disease ( Portal et al, 2018 ), however, a recent Cochrane meta-analysis of five limited trials did not indicate that ω-3 PUFA dietary supplementation is beneficial for CF patients ( Watson and Stackhouse, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 and omega-6 PUFAs are metabolized into different classes of bioactive lipids. There is accumulating evidence that DHA-derived active metabolites are in part responsible for their beneficial effects in suppressing airway inflammation [ 13 , 18 , 61 , 62 ]. DHA is mainly metabolized by cytochrome P450, COX and LOX enzymes, which generate many active eicosanoids including epoxides and prostaglandins, as well as specialized pro-resolving mediators (SPMs, leukotrienes, lipoxins, resolvins and maresins) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…These metabolites are produced by non-enzymatic oxidation of ARA and via the 15-LOX pathway, respectively. The reduction in the levels of these four eicosanoids is most likely related to the incorporation of the biologically active n-3 fatty acids present in fish oil: eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are incorporated into inflammatory cell membranes decreasing the relative content of ARA [ 47 , 48 ]. We previously reported that fish oil supplementation results in increased EPA and DHA and decreased ARA in lung tissue from these rats [ 49 ].…”
Section: Discussionmentioning
confidence: 99%